2017
DOI: 10.1364/josab.34.002478
|View full text |Cite
|
Sign up to set email alerts
|

Amplified spontaneous emission at 523  μm in two-photon excited rubidium vapor

Abstract: Abstract. Population inversion on the 5D5/2-6P3/2 transition in Rb atoms produced by cw laser excitation at different wavelengths has been analysed by comparing the generated mid-IR radiation at 5.23 μm originating from amplified spontaneous emission (ASE) and isotropic blue fluorescence at 420 nm. Using a novel method for detection of two photon excitation via ASE, we have observed directional coand counter-propagating emission at 5.23 μm. Evidence of a threshold-like characteristic is found in the ASE depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Our experimental study of the temporal behaviour of the frequency up-converted field is conducted using a standard experimental arrangement for new optical field generation described in recent papers [9,16]. The optical scheme of our experiment is shown in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experimental study of the temporal behaviour of the frequency up-converted field is conducted using a standard experimental arrangement for new optical field generation described in recent papers [9,16]. The optical scheme of our experiment is shown in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%
“…In Rb atoms, for example, combined stepwise and two-photon excitation to the 5D5/2 energy level, as shown in Figure 1a, produces population inversion on the dipole-allowed 5D5/2-6P3/2 transition because the spontaneous decay probability from the 6P3/2 level is higher than that from the 5D5/2 to 6P3/2 levels [15]. If both the excitation rate and the atom number density in the pencil-shaped interaction region are sufficiently high, mirrorless lasing occurs at 5.23 μm [16] due to the process of amplified stimulated emission (ASE) [17,18]. Mixing of the generated forward-directed mid-IR radiation with the copropagating applied laser fields produces collimated blue light (CBL) at 420 nm by the process of parametric four-wave mixing (FWM) in the direction that satisfies the phase-matching condition [4,19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, frequency up-and down-conversion, i.e. new field generation, due to nonlinear processes in alkali vapors excited with cw low-power (less than 100 mW), resonant laser light received considerable attention [7][8][9][10][11] due to numerous promising applications, including quantum memory [12] and correlated-photon generation [13]. It was shown that generation of directional laser-like radiation can be attributed to four-wave mixing (FWM) and amplified spontaneous emission (ASE) [9,14].…”
mentioning
confidence: 99%
“…In Fig. 3(a), which corresponds to a frequency detuning of δ 776 ≈ −360 MHz, the mid-IR signal is relatively spectrally broad and it presents more similarities with the isotropic blue fluorescence, as expected from ASE [38]. Although a very small CBL signal exists, this regime is dominated by ASE.…”
mentioning
confidence: 83%
“…While CBL was extensively investigated, the study related to the generation of mid-IR photons at 5.23 μm, which is the result of the same process, was generally left apart, mainly due to the fact that conventional Rb cells made of borosilicate or quartz absorb light at 5.23 μm. As such, only very few works have reported on the mid-IR emission at about 5 μm in the context of 4WM [36][37][38]. In these works, the two pumping photons were co-propagating, and the emission of directional mid-IR light in the forward and in the backward direction was reported.…”
mentioning
confidence: 99%